EVALUASI SEKOLAH SATU ATAP TERPADU DENGAN MENGGUNAKAN ANALISIS SWOT-ANALYTIC NETWORK PROCESS (STUDI KASUS DI KABUPATEN PURWAKARTA) - Perwira, Abi Revyansah; Kharisma, Bayu (Buletin Studi Ekonomi, 2019)
Abstract: Integrated One-Stop School Evaluation Using Analysis SWOT-Analytic Network Process (Case Study in Purwakarta Regency). One way to reduce dropout rates is through a Sekolah Satu Atap Terpadu. One of the regencies in West Java that has organized a Sekolah Satu Atap Terpadu as well as the object of this research is Purwakarta regency. By using SWOTAnalytic Network Process (ANP) analysis, this study seeks to evaluate while providing alternative policies for the development of Sekolah Satu Atap Terpadu in Purwakarta regency. The data in this study were obtained by filling out questionnaires by respondents online through Google Form, where respondents were actors who were directly involved in the implementation of a Sekolah Satu Atap Terpadu. From the analysis results obtained Strengths and Threats occupy the highest value. Strengths include students could continue their education up to junior high school level and local government supports both in terms of budget and curriculum. While Threats, among others, school management has become more complex and the delegation of authority from the central and regional governments is not clear. Therefore, the ST strategy can be used as an alternative policy in increasing Strengths and minimizing Threats. Keywords: Sekolah Satu Atap Terpadu; SWOT Analysis; Analytic Network Process (ANP).